Estimating the effects of financial access on poor farmers in rural northern Nigeria - Terfa Williams Abraham (Financial Innovation, 2018)
By recognizing the gap in the literature in examining the effects of financial resources and development outcomes at the household level, this paper examines whether the poorest income quintile would benefit most from programs aimed at increasing their access to financial services in rural northern Nigeria. Most households from this part of the world consist of farmers and, hence, are exposed to the vagaries of climate change. The data from 320 questionnaires administered in two rural communities (Rijau and Fakai) were analyzed using an ordered logit regression model. The results showed that access to financial services by using formal financial institutions and farmer savings clubs benefits vulnerable farmers (mostly women). The robustness check using the Brant test also confirmed that the parallel regression assumption of the model was not violated. A policy scenario that seeks to increase the delivery of financial services to rural farm households using community savings clubs and microfinance institution reforms for reaching the financially underserved was also found to benefit the poorest income quintile, hence, bringing them out of poverty.
Keywords: 650; Rural households; Farm income; Climate change; Financial inclusion